2014
DOI: 10.2146/ajhp130640
|View full text |Cite
|
Sign up to set email alerts
|

Using failure mode and effects analysis to improve the safety of neonatal parenteral nutrition

Abstract: FMEA was useful for detecting medication errors in the PN preparation process and enabling corrective measures to be taken. A checklist was developed to reduce errors in the most critical aspects of the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 15 publications
1
40
0
4
Order By: Relevance
“…Applying method insights resulted in a remarkable organizational attitude and practice shift towards a top safety level. Our work, similarly to other studies using FMEA methodology [15, 16], showed that FMEA prioritizes the potential harms and minimizes riskiness of complex processes.
Fig 2The cascade of methodology- process- outcome
…”
Section: Discussionsupporting
confidence: 80%
“…Applying method insights resulted in a remarkable organizational attitude and practice shift towards a top safety level. Our work, similarly to other studies using FMEA methodology [15, 16], showed that FMEA prioritizes the potential harms and minimizes riskiness of complex processes.
Fig 2The cascade of methodology- process- outcome
…”
Section: Discussionsupporting
confidence: 80%
“…The six intervention types included: technology (n = 38), organizational (n = 16), [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] personnel (n = 13), [72][73][74][75][76][77][78][79][80][81][82][83][84] pharmacy (n = 9), [85][86][87][88][89][90][91][92][93] hazard and risk analysis (n = 8), 10,[93][94][95][96][97][98][99] and multifactorial (i.e. a combination of any of the previous themes; n = 18).…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…Development of preformatted medication order sheets [56][57][58][59][60][61][62][63][64] Medication distribution and supply (n = 6) Preparation of prediluted medications for administration [65][66][67][68][69][70] Nurse prescribing (n = 1) Transcription of paper-based orders to electronic orders by nursing staff 71 Personnel (n = 13) Staff education (n = 13) Personalized feedback of medication prescribing errors [72][73][74][75][76][77][78][79][80][81][82][83][84] Pharmacy (n = 9) Ward based (n = 6) Interventions identified through introduction of ward-based paediatric/neonatal clinical pharmacy service [85][86][87][88][89][90] Dispensary based (n = 3) Interventions identified through dispensary-based pharmacy service [91][92][93] Hazard and risk analysis (n = 8) Quality improvement tools (n = 4) Use of failure modes, effects, and criticality analyses to redesign care processes 10,[95][96][97] Error detection tools (n = 3) Automated detection of medication errors 93,…”
Section: Intervention Type Example Of Intervention Referencesmentioning
confidence: 99%
“…Asefzadeh (2011) in his study identified 48 potential failure modes using FMEA and found that the highest PRN in the respiratory care process was related to the inactive alarm system of the ventilator (PRN = 288); negligence and malpractice, the lack of providing proper training to the employees, and employees' fatigue caused were the cause (21). In their study, Arenas Villafranca et al (2014) (22) found 82 potential failure modes. The processes with the highest PRNs were transcription of the medication orders, formulation of the neonatal parenteral nutrition, and preparation of materials for the formulation.…”
Section: Discussionmentioning
confidence: 94%